Design and Construction of Automatic Mineral Water Refilling System Using Fuzzy Logic - Riga Sahputra Dewa; Desmira Desmira; Irwanto Irwanto (Journal of Engineering, Electrical and Informatics, 2026)
This research discusses the design and construction of an automatic mineral water refilling system using fuzzy logic based on the ESP32 microcontroller. The background of this research is the increasing environmental pollution due to the use of disposable plastic mineral water bottles in the campus environment. The system is designed to be able to fill water containers automatically with IR sensor-based control and ultrasonic sensors to detect the presence of containers and water levels. The research method used is the Waterfall method which includes the planning, design, implementation, and system testing stages. The test results show that the system is able to fill water with an average effective volume of 83.2 % of the container capacity, with a safe limit for automatic stopping at a distance of less than 2 cm from the rim of the container. The implementation of Mamdani fuzzy logic allows the system to make filling decisions based on sensor conditions adaptively, resulting in efficient and accurate pump control. Thus, this system can be an innovative solution to reduce plastic waste while supporting efficient water use in the campus environment.